2006
DOI: 10.1002/bsl.726
|View full text |Cite
|
Sign up to set email alerts
|

Suicide‐related behavior after psychiatric hospital discharge: implications for risk assessment and management

Abstract: Suicide-related behavior (SRB), including suicide attempts and instrumental SRB, occurs far more often than completed suicide and exacts a toll on patients, their loved ones, and society. Nevertheless, few prospective studies of SRB have been conducted. In this study, 954 patients were interviewed in a psychiatric hospital and then followed for one year after discharge. During this one-year period, nearly one-quarter of patients (23%) engaged in SRB, with the rate of suicide attempts (18%) three times greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
3
21
1
Order By: Relevance
“…An increased risk was also found in patients who had a history of psychiatric hospitalisation before their index admission and during readmissions after their index discharge. These findings are supported by two previous studies (33,100). The most plausible explanation for these findings is that those patients considered to be at high risk for suicidal behaviour were given more frequent outpatient consultations and/or were returned to psychiatric inpatient care.…”
Section: Self-harm-induced Somatic Admissions and Follow-up Treatmentssupporting
confidence: 85%
See 4 more Smart Citations
“…An increased risk was also found in patients who had a history of psychiatric hospitalisation before their index admission and during readmissions after their index discharge. These findings are supported by two previous studies (33,100). The most plausible explanation for these findings is that those patients considered to be at high risk for suicidal behaviour were given more frequent outpatient consultations and/or were returned to psychiatric inpatient care.…”
Section: Self-harm-induced Somatic Admissions and Follow-up Treatmentssupporting
confidence: 85%
“…This was a registerbased study of all patients discharged during 1 year from all psychiatric hospitals in England, and outcome data included somatic and psychiatric hospital admissions due to self-harm within 12 months after psychiatric discharge (17). In addition, the literature search identified four interview studies of unselected cohorts, which provided data on self-reported self-harm after discharge from psychiatric hospitals (33,(66)(67)(68). Five interview studies included data on selfreported self-harm after discharge of patients whose psychiatric index admission was related to self-harm (irrespective of suicide intent) (14,15,(69)(70)(71).…”
Section: Studies Of Self-harm After Psychiatric Dischargementioning
confidence: 99%
See 3 more Smart Citations